Composite solid electrolyte and preparation method, battery
By using composite materials of nanosheets and halogen-containing solid electrolytes in the dry process, the problem of low Young's modulus of halide solid electrolyte membrane is solved, and a composite solid electrolyte with high conductivity and high mechanical strength is achieved, which simplifies the preparation process and reduce costs.
Patent Information
- Application Number
- CN202410948509.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-16
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-07-16
AI Technical Summary
When the prior art is difficult to prepare a halide solid electrolyte membrane in a dry process, Young's modulus is low, the morphology and performance are easily affected, which affects the performance of the electrolyte membrane. The preparation process is complicated and the cost is high.
Using composite materials of nanosheets and halogen-containing solid electrolytes, the nanosheets are composed of inorganic oxides, providing high mechanical properties and ion conductivity. The composite solid electrolyte is prepared through non-destructive mixing and pressing processes to avoid fibrosis and ensure stable performance. .
The high conductivity and high mechanical strength of the composite solid electrolyte are achieved, the preparation process is simplified, the production cost is reduced, and the production efficiency is improved, the safety and energy density of the battery are improved.
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a composite solid electrolyte and a preparation method thereof, and a battery using the composite solid electrolyte. Background Art
[0002] With the rapid development of new energy technologies, solid-state batteries have become one of the main directions of future energy development. Composite solid electrolytes have become a hot topic and focus of related research. How to achieve high lithium ion conductivity and high mechanical strength of composite solid electrolytes while achieving a simple preparation process has become an urgent problem to be solved.
[0003] At the same time, the dry process is a new type of battery manufacturing process that has gradually attracted widespread attention in the past two years. Many researchers have chosen to use the dry process to prepare electrodes, mixing active materials, conductive materials, binders, etc. into mixed powders, extruding and rolling to form a continuous self-supporting dry coating, and pressing the coating with the collector to form an electrode sheet. This dry electrode preparation process is simple, has no drying process, is more flexible, and is environmentally friendly. It can effectively save materials, time, and labor costs, avoids long-term high-temperature, ultra-low vacuum drying and dehydration processes, and reduces product energy consumption while increasing the product's cycle life.
[0004] At present, there are also reports on the use of dry process to prepare solid electrolyte membranes. Among them, since halide solid electrolytes show unstable properties to most organic solvents, dry process is of special significance for the preparation of halide solid electrolyte membranes. How to prepare halide solid electrolyte membranes by dry process is of great significance for the industrial application of halide solid electrolytes.
[0005] However, the Young's modulus of halide solid electrolyte is low, and its morphology and performance are easily affected during the fiberization process of the dry process, which affects the performance of the halide solid electrolyte membrane. Summary of the invention
[0006] In order to solve the above problems, the present application discloses a composite solid electrolyte and a preparation method thereof, as well as a battery using the composite solid electrolyte. The composite solid electrolyte has both high conductivity and high mechanical strength, and the preparation process is simple. The production efficiency is improved while the production cost is reduced.
[0007] The first aspect of the present application discloses a composite solid electrolyte, which may include a nanosheet and a halogen-containing solid electrolyte, wherein the nanosheet may be composed of an inorganic oxide, accounting for 5-30% by mass in the composite solid electrolyte.
[0008] In the present application, the nanosheets may have a certain hardness, and may provide higher mechanical properties for the composite solid electrolyte when participating in the formation of the composite solid electrolyte.
[0009] According to some embodiments of the present application, the inorganic oxide may include oxides of one or more metals.
[0010] According to some embodiments of the present application, the metal may include aluminum, titanium and / or zirconium.
[0011] In the present application, the nanosheet may also be an electrolyte material having ion conductivity, and when participating in the formation of the composite solid electrolyte, it may provide higher ion transmission performance.
[0012] According to some embodiments of the present application, the inorganic oxide may include lithium element.
[0013] According to some embodiments of the present application, the inorganic oxide has lithium ion conductivity, and the room temperature lithium ion conductivity is ≥10 -6 S / cm and the Young's modulus of the nanosheets is greater than 80 GPa.
[0014] According to some embodiments of the present application, the size of the nanosheet in the thickness direction may be 3nm-200nm, and the ratio of the thickness of the nanosheet to the thickness of the composite solid electrolyte is 150-2000.
[0015] In the present application, the halogen-containing solid electrolyte constitutes another component of the composite solid electrolyte, which has excellent ionic conductivity and electrochemical stability, and can be used as an electrolyte material to improve the safety and energy density of batteries such as solid-state batteries.
[0016] According to some embodiments of the present application, the halogen-containing solid electrolyte includes a halide solid electrolyte, and the halide solid electrolyte has lithium ion conductivity, and the room temperature lithium ion conductivity is ≥10 -5 S / cm.
[0017] According to some embodiments of the present application, the composite solid electrolyte may further include a binder, and no fiberization process occurs when the binder participates in the composition of the composite solid electrolyte.
[0018] According to some embodiments of the present application, the composite solid electrolyte further includes a binder, and the content of the binder having a fibrillated structure in the binder does not exceed 10% of the total amount of the binder.
[0019] In the present application, the binder involved in forming the composite solid electrolyte may not be subjected to fiberization, thereby eliminating the need for a high shear process and avoiding damage to other components.
[0020] The second aspect of the present application provides a method for preparing a composite solid electrolyte as described above, and the preparation method may include: mixing nanosheets and solid electrolytes under non-destructive conditions to obtain a mixture; pressing the mixture to prepare the composite solid electrolyte; the analytical statistical properties of the halide solid electrolyte do not change under non-destructive conditions; the analytical statistical properties include one or more of average particle size, density, gram capacity, and surface area.
[0021] A third aspect of the present application provides a battery, which may include the composite solid electrolyte as described above.
[0022] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION
[0023] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art to which the present application belongs. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. The words "include" or "comprises" and the like used herein mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects. The terms "and / or" or "and / or" used herein include any and all combinations of one or more related listed items.
[0025] At present, the preparation methods of composite solid electrolytes may include the following: the first is to prepare raw materials such as one or more solid electrolytes and a fiberizable binder for fiberization and then press. However, in this method, in order to ensure the electrochemical properties of the product, the fiberized binder is usually added in a small amount, and the mechanical properties of the binder fiber itself after blowing are poor, so the mechanical properties of the composite solid electrolyte formed as a whole are very poor. In addition, the high shear force in the preparation process will also have a certain negative effect on the solid electrolyte. The second is to use a three-dimensional organic fiber network with a woven structure as a matrix, and then infuse the solid electrolyte raw material into it, and then press it. The composite electrolyte obtained by this method has good mechanical properties. However, the solid electrolytes involved in the process, such as halide solid electrolytes, are incompatible with conventional organic solvents. If a halide solid electrolyte is selected as a raw material, most of them need to be infused by dry method. This is not only difficult to process, but also easy to compound unevenly, resulting in a decrease in electrochemical performance. Even if a small part can be infused by wet method, the conductivity will be partially lost, and it also involves the use of toxic and harmful solvents, which is not suitable for industrial large-scale production.
[0026] The composite solid electrolyte disclosed in the present application simplifies the manufacturing process by selecting components while ensuring the performance of the final product.
[0027] Some preferred embodiments of the present application are described below. It should be noted that the following description is for the purpose of illustration and is not intended to limit the scope of protection of the present application. The steps involved in the present application can be performed accurately in sequence, or various steps can be processed in reverse order or simultaneously. At the same time, other operations can also be added to these processes, or one or more operations can be removed from these processes.
[0028] The present application discloses a composite solid electrolyte, which can be formed by a composite of nanosheets and a halogen-containing solid electrolyte. The sheet structure of the nanosheet can improve the mechanical properties of the composite solid electrolyte, reduce the process requirements of the high shear process, and avoid the damage to the solid electrolyte material during the fiberization process.
[0029] The size of the nanosheet may be 3nm-200nm in the thickness direction. Optionally or preferably, the size of the nanosheet may be 5nm-180nm in the thickness direction. Optionally or preferably, it may be 10nm-150nm. Optionally or preferably, it may be 50nm-100nm. Alternatively, the size of the nanosheet may be any value in the above numerical range in the thickness direction, for example, it may be 3nm, 4nm, 5nm, 7nm, 10nm, 25nm, 50nm, 100nm, 150nm, 200nm, etc. The lateral dimension of the nanosheet is defined as the distance between the two farthest points in the plane, then the lateral dimension may be 1μm-40μm. Optionally or preferably, the lateral dimension of the nanosheet may be 2μm-30μm. Optionally or preferably, it may be 10μm-20μm. Alternatively, the lateral size of the nanosheet may be any value in the above numerical range, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, etc. The size of the nanosheet may also be expressed as a lateral thickness ratio, which may refer to the ratio of the lateral size of the nanosheet to the thickness, which may be 10-200. For example, assuming that the thickness of the nanosheet is 100 nm, that is, 0.1 μm, when the lateral thickness ratio is 40 or 200, the lateral size of the nanosheet may be 50 nm or 20 μm.
[0030] In some embodiments, the thickness ratio of the nanosheet to the composite solid electrolyte (e.g., referred to as a membrane thickness ratio) may be 150-2000. Alternatively or preferably, the membrane thickness ratio may be 500-1500. Alternatively or preferably, the membrane thickness ratio may be 800-1000. Alternatively, the membrane thickness ratio may be any value in the above numerical range, such as 800, 1000, 2000, etc.
[0031] In some embodiments, the nanosheet may be selected from inorganic oxides. Optionally or preferably, the inorganic oxide may include oxides of one or more metals. The metal includes, but is not limited to, aluminum (Al), zinc (Zn), titanium (Ti), magnesium (Mg), calcium (Ca), zirconium (Zr), chromium (Cr), hafnium (Hf), cobalt (Co), barium (Ba), lead (Pb), vanadium (V), iron (Fe), manganese (Mn), etc. or any combination thereof. The metal may also include one or more of the lanthanide metals, for example, lanthanum (La), scandium (Sc), yttrium (Y), Ce (cerium), Nd (neodymium), Gd (gadolinium), Dy (dysprosium), etc. Optionally or preferably, the metal may include one or more of aluminum, titanium and / or zirconium. The nanosheet may be one or more of aluminum oxide nanosheets, titanium oxide nanosheets, and zirconium oxide nanosheets.
[0032] The nanosheets may also be inorganic non-metallic oxide nanosheets, for example, silicon oxide nanosheets or graphene oxide nanosheets.
[0033] In some embodiments, the inorganic oxide may include lithium. Also, the inorganic oxide may have lithium ion conductivity. Exemplarily, the room temperature lithium ion conductivity (referred to as IC1) of the inorganic oxide may be IC1≥10 -6 S / cm. Optionally or preferably, the IC1 of the inorganic oxide is ≥10 -5 S / cm. Optionally or preferably, the IC1 of the inorganic oxide is ≥10 -4 S / cm. It is understood that when the inorganic oxide includes lithium and has lithium ion conductivity, it can be a lithium ion oxide solid electrolyte. As an example, the lithium ion oxide solid electrolyte can be a NASICON type solid electrolyte such as LiTi2(PO4)3 or its element substitution body, a perovskite type solid electrolyte such as (LaLi)TiO3, a Li 14 ZnGe4O 16 , LISICON type solid electrolytes such as Li4SiO4, LiGeO4 or their element substitution bodies, Li7La3Zr2O 12 Or a garnet-type solid electrolyte such as an element substitution body thereof, or Li3PO4 or its N substitution body, etc. Optionally or preferably, the inorganic oxide may include one or more of LLZO, LLTO, LAGP, LATP, LBSPO, LPO, Li4SiO4, Li2ZnTi3O8, and / or one or more of its derivatives. The use of lithium ion oxide solid electrolyte nanosheets can, on the one hand, provide a certain structural strength for the composite solid electrolyte (due to the good mechanical strength of lithium ion oxide solid electrolytes), and on the other hand, can improve the ion transport performance of the composite solid electrolyte.
[0034] The derivatives of the above lithium ion oxide solid electrolytes may include doped derivatives. For example, the introduction of other metal ions including but not limited to vanadium, cobalt, nickel, etc. can adjust the electrochemical properties and structural stability. The above derivatives may also include composite derivatives. For example, a composite formed by combining a lithium ion oxide solid electrolyte with other materials such as sulfides, high molecular polymers, etc. can improve conductivity, mechanical strength and chemical stability. The above derivatives may also include modified derivatives obtained after surface modification. For example, modifying or coating a layer of protective materials such as carbon nanotubes on the surface of a lithium ion oxide solid electrolyte can improve interface stability and electrochemical performance.
[0035] It can be understood that the nanosheet can be used to improve the mechanical strength of the composite solid electrolyte. When the nanosheet is selected as one or more of the above exemplary embodiments, the Young's modulus of the nanosheet can be greater than 80GPa. For example, 80GPa, 82GPa, 84GPa, 88GPa, 90GPa, 92GPa, 94GPa, 96GPa, 98GPa, 100GPa, etc. or an increment of any of the aforementioned values. Since the Young's modulus of another component of the composite solid electrolyte, that is, the halogen-containing solid electrolyte, is generally small, for example, less than 50GPa, the use of a hard inorganic oxide material and a soft halide solid electrolyte can further improve the mechanical strength of the composite solid electrolyte.
[0036] In some embodiments, the mass fraction of the nanosheets in the composite solid electrolyte may be 5-30wt%. Alternatively or preferably, the mass fraction of the nanosheets may be 10-25wt%. Alternatively or preferably, the mass fraction of the nanosheets may be 15-20wt%. Alternatively, the mass fraction of the nanosheets may be any value in the above numerical range, such as 5wt%, 15wt%, 20wt%, 30wt%, etc.
[0037] Any suitable preparation method can be used to obtain the above-mentioned nanosheets, including but not limited to liquid phase exfoliation method, such as dispersing bulk inorganic oxide materials (e.g., titanium dioxide) in a suitable solvent (e.g., water, ethanol, N-methylpyrrolidone (NMP), etc.) and using ultrasonic treatment to exfoliate the material into nanosheets in the solvent and then centrifuge to obtain them; hydrothermal / solvothermal method, such as dissolving an inorganic oxide precursor (e.g., a metal salt) in water or an organic solvent to obtain a solution and reacting it under high temperature and high pressure conditions provided by a high-pressure reactor to obtain inorganic oxide nanosheets; chemical vapor deposition method, such as introducing a gaseous precursor (e.g., a metal organic compound) into a reaction chamber and then reacting it under controlled reaction conditions (e.g., temperature, gas flow rate, etc.) The inorganic oxide nanosheets are decomposed on the substrate surface under the condition of low concentration (e.g., high amount, etc.), solution chemical synthesis method, such as using metal salts and oxidants to react chemically in solution to generate inorganic oxide nanosheets, template method, such as immersing the inorganic oxide precursor solution into a suitable template material (e.g., porous membrane, graphene oxide, etc.) and then generating inorganic oxide nanosheets on the template through chemical reaction or electrochemical deposition, ion exchange method, such as immersing layered inorganic compounds (such as layered double hydroxides) in a solution containing target metal ions and then generating target inorganic oxide nanosheets through ion exchange reaction, mechanical pulverization method, such as using mechanical pulverization equipment / technology to process bulk inorganic oxide materials to obtain inorganic oxide nanosheets, etc. The above are only examples, and other methods that can achieve the same purpose are applicable to this application.
[0038] The halogen-containing solid electrolyte may include a halide solid electrolyte. Exemplarily, the halide solid electrolyte may have lithium ion conductivity. Similarly or similarly, the room temperature lithium ion conductivity of the halide solid electrolyte is expressed by IC2, which may be IC2≥10 -5 S / cm. Optionally or preferably, the IC2 of the halide solid electrolyte is ≥10 -4 S / cm. Optionally or preferably, the IC2 of the halide solid electrolyte is ≥10 -3 S / cm. Optionally or preferably, the IC2 of the halide solid electrolyte is ≥10 -2 In some embodiments, the halide solid electrolyte may include a lithium halide solid electrolyte having a chemical formula of Li a MX b Indicates, M represents a metal element or a metalloid element, and X represents a halogen element. Among them, "metalloid element" can represent an element with similar metal properties, which may include B, Si, Ge, As, Sb, Te, etc. Optionally or preferably, M may include but is not limited to Al, Zn, Mg, Ca, Ba, Mn, Cd, Co, Yb, Y, Cr, In, Ga, Sr, Hf, Ti, Ta, Sn, Nb, Er, Sc, etc. or any combination thereof. Optionally or preferably, M may include one or more of Y, In, Zr, Ga, and Sc. In some embodiments, the halide solid electrolyte may be Li2ZrCl6 or a derivative thereof. The derivative of Li2ZrCl6 can be achieved by aisovalent substitution or doping modification of Li2ZrCl6. For example, the derivative Li2ZrCl obtained by partially replacing chlorine (Cl) with fluorine (F) 6-x F x , which can improve the ionic conductivity and electrochemical stability of the material; or, by partially replacing chlorine (Cl) with bromine (Br), the derivative Li2ZrCl 6-x Br x , which can improve the ionic conductivity and thermal stability of the material; or, by partially replacing chlorine (Cl) with iodine (I), the derivative Li2ZrCl 6-x I x , which can further improve the ionic conductivity of the material. For example, derivatives obtained by doping other metal elements such as Al, Ga, Ti, In, Y, Dy, Nb, Mn, Sc, Bi, etc. to replace part of Zr , the crystal structure and ionic conductivity of the material can be optimized. The derivatives of Li2ZrCl6 can also be achieved through material compounding. The derivatives of Li2ZrCl6 can also be achieved through chemical modification. For example, through surface modification such as coating Li2ZrCl6 with a conductive polymer or other protective layer, the interface stability and electrochemical performance of Li2ZrCl6 can be improved; or, through chemical cross-linking technology, the structural stability and ionic conductivity of Li2ZrCl6 can be enhanced.
[0039] In some embodiments, the halide solid electrolyte may participate in the formation of the composite solid electrolyte in a granular form. Optionally or preferably, the particle size (in terms of average particle size Dv50) of the granular halide solid electrolyte may not exceed 15 μm. Optionally or preferably, the particle size Dv50 of the halide solid electrolyte particles may not exceed 14 μm. Optionally or preferably, the particle size Dv50 of the halide solid electrolyte particles may not exceed 13 μm. Optionally or preferably, the particle size Dv50 of the halide solid electrolyte particles may not exceed 12 μm. Optionally or preferably, the particle size Dv50 of the halide solid electrolyte particles may not exceed 11 μm. Optionally or preferably, the particle size Dv50 of the halide solid electrolyte particles may not exceed 10 μm.
[0040] An exemplary process for preparing the above-mentioned halide solid electrolyte particles can be as follows: Taking the preparation of Li2ZrCl6 particles as an example, raw material powders are prepared according to a molar ratio or an adjusted molar ratio, for example, a molar ratio determined by taking into account factors such as raw material consumption, including LiCl raw material powder and ZrCl4 raw material powder. Necessary additives such as stabilizers can be added at the same time. The raw materials can be placed in a ball mill such as a planetary ball mill or other mixing equipment for thorough mixing to obtain a mixed reactant with uniformly distributed components. The mixed reactants can be heated and melted in a vacuum or inactive atmosphere to obtain a completely reacted and homogenized molten product. Rapid cooling of the molten product (for example, quenching, introducing the molten product into a cooling medium such as water or liquid nitrogen) can form a solid material with a glassy or amorphous structure. The solid material can be transferred to a pulverizing device such as a ball mill or a crusher for pulverization to obtain a granular final product. The particles are classified by a screening device to obtain halide solid electrolyte particles of a desired particle size range.
[0041] In some embodiments, the mass fraction of the halogen-containing solid electrolyte in the composite solid electrolyte may be 65-94wt%. Alternatively or preferably, the mass fraction of the halogen-containing solid electrolyte may be 69-84wt%. Alternatively or preferably, the mass fraction of the halogen-containing solid electrolyte may be 74-80wt%. Alternatively, the mass fraction of the halogen-containing solid electrolyte may be any value in the above numerical range, for example, 69%, 80%, 84.8%, etc.
[0042] Furthermore, the composite solid electrolyte may also include a binder. The binder does not undergo a fiberization process when participating in the composition of the composite solid electrolyte. In the present application, the "composition" of the composite solid electrolyte can be understood as the preparation process of the composite solid electrolyte, including the raw material preparation stage, that is, before preparation, during the preparation process, and after the preparation is completed, and / or the subsequent use of the composite solid electrolyte. In other words, before and after the preparation of the composite solid electrolyte, the binder participates in the entire process without interference or substantially without interference, and its own characteristics or performance or properties or structure will not change. It can also be said that the binder does not undergo high shear, does not form a fibrous structure during the entire process, and does not fiberize. Based on this, any known binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, polyethylene, polypropylene, aramid resin, polyamide, polyimide, polyamide-imide, polyacrylonitrile, polyacrylic acid, polymethyl acrylate, polyethyl acrylate, polyhexyl acrylate, polymethacrylic acid, polymethyl methacrylate, polyethyl methacrylate, polyhexyl methacrylate, polyvinyl acetate, polyvinyl pyrrolidone, polyether, polyether sulfone, polyhexafluoropropylene, styrene-butadiene rubber, carboxymethyl cellulose, etc. or any combination thereof can be used for the present application. Copolymers can also be used as binders, and exemplary ones can be copolymers of two or more materials selected from tetrafluoroethylene, hexafluoroethylene, hexafluoropropylene, perfluoroalkyl vinyl ether, vinylidene fluoride, trifluorochloroethylene, ethylene, propylene, pentafluoropropylene, fluoromethyl vinyl ether, acrylic acid, hexadiene, etc. Alternatively, a mixture of two or more materials in the above examples can also be used as a binder.
[0043] It is understandable that, because the present application expects to avoid destructive fiberization processes rather than expecting to avoid fibrillated structures, a small amount of fibrillated structures formed during the mixing process of the halide solid electrolyte and the binder should still be regarded as the scope of protection of the present application. In some embodiments, the content of the binder with a fibrillated structure in the binder does not exceed 10% of the total amount of the binder. Alternatively or preferably, the content of the binder with a fibrillated structure in the binder does not exceed 7% of the total amount of the binder. Alternatively or preferably, the content of the binder with a fibrillated structure in the binder does not exceed 5% of the total amount of the binder. Alternatively or preferably, the content of the binder with a fibrillated structure in the binder does not exceed 3% of the total amount of the binder. Alternatively or preferably, the content of the binder with a fibrillated structure in the binder does not exceed 2% of the total amount of the binder. Alternatively or preferably, the content of the binder with a fibrillated structure in the binder does not exceed 1% of the total amount of the binder. Alternatively, the binder with a fibrillated structure in the binder accounts for any value within the above numerical range.
[0044] As an example only, and not a limitation of the scope of protection, the content of the binder with a fibrillated structure in the total binder can be obtained by taking electron microscopy pictures. For example, a uniformly mixed electrolyte membrane is photographed under an electron microscope, and the area of the binder with a fibrillated structure is cut off, and the area ratio is compared with the area of the entire electrolyte membrane or the cut part of the electrolyte, and the area ratio is the ratio of the binder with a fibrillated structure to the total amount of the binder.
[0045] Further preferably, the composite solid electrolyte does not contain a binder having a fibrillated structure.
[0046] It should be noted that the above examples of adhesives are only for illustrative purposes and are not intended to limit the protection scope of the technical solution of this application. Any adhesive obtained by adjustment / modification / update without violating the inventive concept of this application is within the protection scope of this application.
[0047] In some embodiments, the mass fraction of the binder in the composite solid electrolyte may be 0.2-5wt%. Alternatively or preferably, the mass fraction of the binder may be 1-4wt%. Alternatively or preferably, the mass fraction of the binder may be 2-3wt%. Alternatively, the mass fraction of the binder may be any value in the above numerical range, such as 0.2wt%, 1wt%, 5wt%, etc.
[0048] Optionally or preferably, the composite solid electrolyte may be in the form of a film or a block, and its thickness may be 1-100 μm. Optionally or preferably, the thickness of the composite solid electrolyte may be 1-80 μm; optionally or preferably, the thickness of the composite solid electrolyte may be 40-60 μm; further optionally or preferably, further, the thickness of the composite solid electrolyte is 5-20 μm. Alternatively, the thickness of the composite solid electrolyte may be any value in the above numerical range, such as 40 μm, 80 μm, 100 μm, etc.
[0049] The present application also discloses a method for preparing the composite solid electrolyte, which may include the following exemplary steps.
[0050] In the first step, the nanosheets and the halogen-containing solid electrolyte are mixed under non-destructive conditions to obtain a mixture.
[0051] In one feasible embodiment, the nanosheets and the halogen-containing solid electrolyte can be mixed to obtain a mixture. The mixing can be dry mixing, which can be carried out under a non-destructive process. For illustrative purposes only, a non-destructive process can refer to a process in which the material is not modified or substantially not modified during the process. Therefore, the characteristics, properties, structure, etc. of the material will be the same or almost the same as the material not subjected to the process. An example is that the binder will not undergo a fiberization process during mixing. The non-destructive process can be carried out at a lower mixing speed to avoid a high shear process. Any suitable mixer can be used for the mixing process.
[0052] Non-destructive mixing processes are known in the prior art. It can be understood that due to the use of inorganic oxide nanosheets with a certain Young's modulus, the destructive fiberization process is no longer forced to be performed during the preparation of the composite solid electrolyte. Therefore, the traditional solid-phase mixing process can be applied to the present application, such as stirring mixing and airflow mixing.
[0053] However, the present application does not exclude the use of certain processes with a certain shear force that do not harm the halide solid electrolyte. As an illustrative example only, rather than a limitation on the scope of protection, the process may include high-speed dispersion or air flow fragmentation.
[0054] Preferably, the rotation speed of the high-speed dispersion is lower than 10000 rpm, such as 1000 rpm, 2000 rpm, 3000 rpm, 4000 rpm, 5000 rpm, 6000 rpm, 7000 rpm or 7500 rpm, etc., and the time of the high-speed dispersion is less than 30 min, such as 30 min, 25 min, 20 min, 15 min, 12 min, 10 min, 8 min, 6 min, 4 min or 3 min, etc.;
[0055] Preferably, the speed of the high-speed dispersion is 1000 rpm to 10000 rpm;
[0056] Preferably, the speed of the high-speed dispersion is 4500 rpm to 7500 rpm, and the time of the high-speed dispersion is 5 min to 30 min;
[0057] Preferably, the speed of the air flow crushing is 30m / s to 100m / s, for example, 30m / s, 40m / s, 50m / s, 60m / s, 70m / s, 80m / s, 90m / s or 100m / s, etc.; the temperature is 25℃ to 60℃, for example, 25℃, 30℃, 35℃, 40℃, 45℃, 50℃ or 60℃, etc.
[0058] Due to the mechanical support of the inorganic oxide nanosheets, there is no need for an additional fiberization process to fiberize the binder to provide mechanical support, so that the fiberized structure of the binder is no longer necessary.
[0059] It is understandable that the fibrillated structure is known in the art, and refers to a binder having a filamentous and elongated structure similar to a fiber. In a dry process, this fibrillated structure is beneficial to the improvement of the mechanical properties of the membrane.
[0060] One of the purposes of this application is to avoid the use of destructive fiberization processes, rather than excluding the use of binders with fibrillated structures. This application uses inorganic oxide nanosheets to improve the mechanical strength of composite solid electrolytes, so in the preparation process, raw materials can be mixed under non-destructive conditions to avoid the use of fiberization processes. Based on this, the technical solution of using a binder with a fiberized structure to compound inorganic oxide nanosheets and halogen-containing solid electrolytes that meet the requirements of this application and prepare a composite solid electrolyte membrane in a non-destructive mixing process should still be considered within the scope of protection of this application. For example, a PTFE fiber membrane is mixed with a halide solid electrolyte under non-destructive process conditions after a crushing process to obtain a halide solid electrolyte mixture, and the fiberized structure of PTFE also helps to improve the mechanical properties of the solid electrolyte membrane. It can be understood that the fiberized structure is different from the fibrillated structure. The fibrillated structure referred to herein specifically refers to the structure generated by the binder in the destructive fiberization process, and the rod-like structure with a specific aspect ratio that exists without undergoing the fiberization process belongs to the fiberized structure.
[0061] It can be understood that the non-destructive process means that the analytical statistical properties of the halide solid electrolyte do not change during the fiberization process, which can mean no change or changes within a smaller range. Changes within a smaller range mean that the change in the corresponding analytical statistical properties is less than 5%, 4%, 3%, 2% or 1%.
[0062] The analytical statistical properties of the halide solid electrolyte may include one or more of average particle size, density, gram capacity, and surface area.
[0063] Preferably, the statistical properties analyzed simultaneously monitor mean particle size, density, gram capacity, and surface area.
[0064] The second step is to press the mixed material to prepare the composite solid electrolyte.
[0065] In a feasible embodiment, the pressing can be achieved by molding, calendering or rolling to obtain a bulk or film-shaped composite solid electrolyte. Taking the preparation of a composite solid electrolyte membrane by rolling as an example, the mixture obtained in the first step can first be preformed, such as kneading to obtain a bulk precursor. The bulk precursor can be placed in a roller press for hot rolling. The hot rolling can include multiple rolling. For example, multiple rolling can be performed by gradually reducing the roller gap, and the final composite solid electrolyte membrane is obtained after completion. The pressing temperature used in the hot rolling can be higher than the mixing temperature in the first step, or it can be the same. For example, the pressing temperature can be 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, etc. In one example, the pressing temperature can be selected according to different binders. For example, the pressing temperature is different when PVDF is used as a binder and when TPA is used as a binder. The pressing temperature can be 80°C when PVDF is used as a binder, and the pressing temperature can be 140°C when TPA is used as a binder.
[0066] In the preparation process of conventional composite solid electrolytes, the binder needs to be subjected to fiberization treatment, and the fiberization process often causes a certain degree of damage to the component materials due to the high shear force. The preparation method of the composite solid electrolyte disclosed in the present application uses nanosheets to improve the mechanical properties, thereby avoiding the use of high-speed shear fiberization process in the preparation process, preventing damage to other components, and improving the safety of the composite solid electrolyte.
[0067] The present application also discloses a battery, for example, a lithium-ion solid-state battery, wherein the battery comprises a positive electrode, a negative electrode, and a composite solid-state electrolyte located between the positive electrode and the negative electrode.
[0068] The positive electrode may contain a material capable of inserting or extracting metal ions such as lithium ions, such as a positive electrode active material, and examples thereof may include lithium-containing transition metal oxides, transition metal fluorides, polyanionic materials, fluorinated polyanionic materials, transition metal sulfides, transition metal fluorides, transition metal oxysulfides, or transition metal oxynitrides. Examples of lithium-containing transition metal oxides may include Li(NiCoAl)O2 or LiCoO2.
[0069] The negative electrode may also be a material containing metal ions capable of embedding or de-embedding lithium ions, such as a negative electrode active material, which may be exemplified by metal materials, carbon materials, oxides, nitrides, tin compounds, silicon compounds, etc. The metal material may be a metal element or an alloy such as lithium metal or a lithium alloy. The carbon material may be natural graphite, coke, graphitizable carbon, carbon fiber, spherical carbon, artificial graphite or amorphous carbon, etc. The preferred negative electrode active material may be silicon (Si), tin (Sn), germanium (Ge), a silicon compound or a tin compound.
[0070] At least one of the positive electrode or the negative electrode may also contain a conductive additive, for example, a carbon-based material such as graphite (natural graphite or artificial graphite, etc.), carbon black (acetylene black or Ketjen black, etc.), carbon nanotubes, graphene, etc., a metal-based material such as metal powder (aluminum powder, nickel powder, etc.), a metal oxide (titanium oxide, etc.), a metal whisker (aluminum oxide, oxidizing, etc.), etc., a conductive polymer such as polyaniline, polypyrrole, polythiophene, etc., a conductive fiber such as carbon fiber, metal fiber, metal compound fiber, polymer fiber, etc. The conductive additive may also be a mixture of one or more of the above.
[0071] The composite solid electrolyte may be the composite solid electrolyte described above. For details, please refer to the above content.
[0072] The present application is further described in detail below in conjunction with the examples. It should be noted that the following examples are only used to illustrate the present application and are not used to limit the scope of protection claimed in the present application.
[0073] Example 1 - Preparation of composite solid electrolyte membrane
[0074] In this embodiment, the nanosheets are TiO2 nanosheets, the solid electrolyte is Li2ZrCl6, and the binder is PVDF, and the above three are prepared in a mass ratio of 5:94:1.
[0075] The specific process is as follows:
[0076] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 5:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0077] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 94:6, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0078] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 800.
[0079] Example 2-Preparation of composite solid electrolyte membrane
[0080] Compared with Example 1, Example 2 differs in that the mass fraction of the added nanosheets is different.
[0081] In this embodiment, the nanosheets are TiO2 nanosheets, the solid electrolyte is Li2ZrCl6, and the binder is PVDF, and the above three are prepared in a mass ratio of 15:84:1.
[0082] The specific preparation process is as follows:
[0083] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 15:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0084] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 84:16, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0085] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 800.
[0086] Example 3 - Preparation of composite solid electrolyte membrane
[0087] Compared with Example 1, Example 3 differs in that the mass fraction of the added nanosheets is different.
[0088] In this embodiment, the nanosheets are TiO2 nanosheets, the solid electrolyte is Li2ZrCl6, and the binder is PVDF, and the above three are prepared in a mass ratio of 30:69:1.
[0089] The specific preparation process is as follows:
[0090] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 30:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0091] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to a mass ratio of Li2ZrCl6: premix of 69:31, and added into a mixer and mixed to obtain a mixture; wherein the mixing time is 45 min, the speed of the mixer is 1000 r, and the mixing temperature is 20° C. to obtain a uniformly mixed mixture;
[0092] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 800.
[0093] Example 4-Preparation of composite solid electrolyte membrane
[0094] The difference between Example 4 and Example 2 is that the sizes of the added nanosheets are different.
[0095] In this embodiment, the nanosheets are TiO2 nanosheets, the solid electrolyte is Li2ZrCl6, and the binder is PVDF, and the above three are prepared in a mass ratio of 15:84:1.
[0096] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 15:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 200nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 10;
[0097] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 84:16, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0098] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 200.
[0099] Example 5-Preparation of composite solid electrolyte membrane
[0100] The difference between Example 5 and Example 2 is that the membrane thickness of the composite solid electrolyte membrane is different.
[0101] In this embodiment, the nanosheets are TiO2 nanosheets, the solid electrolyte is Li2ZrCl6, and the binder is PVDF, and the above three are prepared in a mass ratio of 15:84:1.
[0102] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 15:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0103] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 84:16, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0104] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 100μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 2000.
[0105] Example 6-Preparation of composite solid electrolyte membrane
[0106] Compared with Example 2, Example 6 differs in that the size of the added nanosheets and the thickness of the composite solid electrolyte membrane are different.
[0107] In this embodiment, the nanosheets are TiO2 nanosheets, the solid electrolyte is Li2ZrCl6, and the binder is PVDF, and the above three are prepared in a mass ratio of 15:84:1.
[0108] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 15:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 100nm, the lateral size was 20μm, and the ratio of the lateral size to the thickness was 200;
[0109] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 84:16, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0110] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 100μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 1000.
[0111] Example 7-Preparation of composite solid electrolyte membrane
[0112] The difference between Example 7 and Example 2 lies in the different types of nanosheets added and the different types of binders.
[0113] In this embodiment, the nanosheet is LLTO nanosheet, the solid electrolyte is Li2ZrCl6, and the binder is thermoplastic polyamide (TPA), and the above three are obtained according to a mass ratio of 15:84:1.
[0114] 1) Premix acquisition: Li 0.33 La 0.57 TiO3 (LLTO) nanosheets and TPA were weighed in a mass ratio of 15:1 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the LLTO nanosheet was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0115] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 84:16, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0116] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 140°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the LLTO nanosheet thickness is 800.
[0117] Example 8-Preparation of composite solid electrolyte membrane
[0118] The difference between Example 8 and Example 7 is that the mass fraction of the added binder is different.
[0119] In this embodiment, the nanosheet is LLTO nanosheet, the solid electrolyte is Li2ZrCl6, and the binder is TPA, and the above three are prepared in a mass ratio of 15:80:5.
[0120] The specific preparation process is as follows:
[0121] 1) Premix acquisition: Li 0.33 La 0.57 TiO3 (LLTO) nanosheets and TPA were weighed in a mass ratio of 15:5 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the LLTO nanosheet was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0122] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 80:20, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0123] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 140°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the LLTO nanosheet thickness is 800.
[0124] Example 9-Preparation of composite solid electrolyte membrane
[0125] The difference between Example 9 and Example 7 is that the mass fraction of the added binder is different.
[0126] In this embodiment, the nanosheet is LLTO nanosheet, the solid electrolyte is Li2ZrCl6, and the binder is TPA, and the above three are prepared according to a mass ratio of 15:84.8:0.2.
[0127] 1) Premix acquisition: Li 0.33 La 0.57 TiO3 (LLTO) nanosheets and TPA were weighed in a mass ratio of 15:0.2 and added to a mixer to obtain a premix; wherein the mixer speed was 1000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the LLTO nanosheet was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0128] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 84.8:15.2, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0129] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 140°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the LLTO nanosheet thickness is 800.
[0130] Comparative Example 1-Preparation of solid electrolyte membrane
[0131] Comparative Example 1 is different from Example 1 in that no oxide nanosheets are added, and the solid electrolyte membrane is formed by mixing PTFE and Li2ZrCl6 through fiberization. The fiberization process is as follows: high-speed stirring speed is 12000r, and temperature is 55°C.
[0132] The specific preparation process is as follows:
[0133] 1) Weigh the raw materials according to the mass ratio of Li2ZrCl6:PTFE of 99:1, add them into the mixer and mix them to obtain a mixture. The mixing time is 30 minutes, the mixer speed is 12000r, and the mixing temperature is 55°C;
[0134] 2) The mixed material is taken out and pre-kneaded to obtain a block, which is then put into a roller press for hot roller pressing at a temperature of 90°C. First, a large roller gap is used for rolling, and then the roller is fed multiple times to gradually reduce the roller gap, and finally a film with a target thickness of 40 μm is obtained.
[0135] Comparative Example 2-Preparation of Solid Electrolyte Membrane
[0136] Compared with Example 1, Comparative Example 2 is different in that no oxide nanosheets are added and the mass fraction of the binder is different.
[0137] The specific preparation process is as follows:
[0138] 1) Mixture acquisition: Li2ZrCl6 and PVDF were weighed in a mass ratio of 94:6 and added into a mixer to obtain a premix; wherein the speed of the mixer was 12000r, the mixing temperature was 20°C, and the initial mixing time was 45min;
[0139] 3) Pressing: Take out the mixed material, pre-knead it into a mass, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, roll it with a large roller gap, then feed the roller multiple times to gradually reduce the roller gap, and finally obtain a film with a target thickness of 40μm.
[0140] Comparative Example 3-Preparation of Solid Electrolyte Membrane
[0141] The difference between Comparative Example 3 and Example 1 is that the mass fraction of the added nanosheets exceeds 30wt%.
[0142] The specific preparation process is as follows:
[0143] 1) Premix acquisition: TiO2 nanosheets and PVDF were weighed in a mass ratio of 40:1 and added to a mixer to obtain a premix; wherein the mixer speed was 12000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The thickness of the TiO2 nanosheets was 50nm, the lateral size was 2μm, and the ratio of the lateral size to the thickness was 40;
[0144] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 59:41, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0145] 3) Pressing: Take out the mixed material, pre-knead it to get a block, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, use a large roller gap state to roll, then feed the roller multiple times, gradually reduce the roller gap, and finally get a membrane with a target thickness of 40μm. The ratio of the composite solid electrolyte membrane thickness to the TiO2 nanosheet thickness is 800.
[0146] Comparative Example 4-Preparation of Solid Electrolyte Membrane
[0147] The difference between Comparative Example 4 and Example 3 is that inorganic oxide nanoparticles are added instead of nanosheets.
[0148] The specific preparation process is as follows:
[0149] 1) Premix acquisition: TiO2 nanoparticles and PVDF were weighed in a mass ratio of 30:1 and added into a mixer to obtain a premix; wherein the mixer speed was 12000r, the mixing temperature was 20°C, and the initial mixing time was 30min. The particle size of the TiO2 nanoparticles was 50nm;
[0150] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to a mass ratio of Li2ZrCl6: premix of 69:31, and added into a mixer and mixed to obtain a mixture; wherein the mixing time is 45 min, the speed of the mixer is 1000 r, and the mixing temperature is 20° C. to obtain a uniformly mixed mixture;
[0151] 3) Pressing: Take out the mixed material, pre-knead it into a mass, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, roll it with a large roller gap, then feed the roller multiple times to gradually reduce the roller gap, and finally obtain a film with a target thickness of 40μm.
[0152] Comparative Example 5-Preparation of Solid Electrolyte Membrane
[0153] Compared with Example 8, the difference is that the added inorganic oxide is low Young's modulus oxide particles.
[0154] The specific preparation process is as follows:
[0155] 1) Obtaining premix: Weigh Li3La(PO4)2 nanoparticles and TPA in a mass ratio of 15:5 and add them into a mixer to obtain a premix; wherein the mixer speed is 12000r, the mixing temperature is 20°C, and the initial mixing time is 30min. The particle size of Li3La(PO4)2 nanoparticles is 500nm;
[0156] 2) Mixture acquisition: Li2ZrCl6 powder is weighed according to the mass ratio of Li2ZrCl6: premix of 80:20, and added into a mixer to continue mixing to obtain a mixture; wherein, the mixing time is 45 minutes, the speed of the mixer is 1000r, and the mixing temperature is 20°C to obtain a uniformly mixed mixture;
[0157] 3) Pressing: Take out the mixed material, pre-knead it into a mass, and put it into a roller press for hot roller pressing at a temperature of 90°C. First, roll it with a large roller gap, then feed the roller multiple times to gradually reduce the roller gap, and finally obtain a film with a target thickness of 40μm.
[0158] Example 10 - Ionic conductivity test
[0159] The solid electrolyte membranes obtained in Examples 1-9 and Comparative Examples 1-5 were punched out into Φ10 discs (whose area was set to S) using a punching machine, and placed in a solid electrolyte test mold, and a pressure of 200MPa was applied, and the pressure was kept constant for 1min. The prepared test mold sample was then connected to the electrochemical workstation for impedance spectrum testing, with the high-frequency zone parameters set to 8MHz and the low-frequency zone parameters set to 100mHz, and the test was started. The test curve was fitted using Z-view software to obtain the impedance value R. After the test was completed, the electrolyte sheet was taken out, the thickness L was measured, and the conductivity was calculated. , unit is mS / cm. The test results are summarized in Table 1.
[0160] Example 11 - Puncture Strength Test
[0161] The solid electrolyte membranes obtained in Examples 1-9 and Comparative Examples 1-5 were used as samples, flattened and clamped in a fixture, the inner diameter of the fixture was 10 mm, the puncture needle size was Φ = 1.0 mm, the fixture was punctured at a rate of 100 ± 10 mm / min, and the force (gf) measured during puncture was recorded. After the test was completed, the sample was taken out, and a 4-point thickness test was performed around the pinhole, the average value was taken, and the puncture strength (gf / mm) was calculated. Puncture strength = force during penetration / thickness of the solid electrolyte membrane. The test results are summarized in Table 1.
[0162] Table 1 Solid electrolyte parameters and test results
[0163] Group Solid electrolyte components Binder Oxide size Solid electrolyte membrane thickness Ionic conductivity S / cm Puncture strength gf / mm 1 <![CDATA[5wt%TiO2+94wt%Li2ZrCl6(TiO2:~282GPa)]]> 1wt%PVDF 50nm / 2μm (lateral thickness ratio 40) 40μm (film / sheet thickness ratio 800) 0.418 65.44 2 <![CDATA[15wt%TiO2+84wt%Li2ZrCl6(TiO2:~282GPa)]]> 1wt%PVDF 50nm / 2μm (lateral thickness ratio 40) 40μm (film / sheet thickness ratio 800) 0.374 81.79 3 <![CDATA[30wt%TiO2+69wt%Li2ZrCl6(TiO2:~282GPa)]]> 1wt%PVDF 50nm / 2μm (lateral thickness ratio 40) 40μm (film / sheet thickness ratio 800) 0.33 83.97 4 <![CDATA[15wt%TiO2+84wt%Li2ZrCl6]]> 1wt%PVDF 200nm / 2μm (lateral thickness ratio 10) 40μm (film / sheet thickness ratio 800) 0.36 83.37 5 <![CDATA[15wt%TiO2+84wt%Li2ZrCl6]]> 1wt%PVDF 50nm / 2μm (lateral thickness ratio 40) 100μm (film / sheet thickness ratio 2000) 0.376 84.65 6 <![CDATA[15wt%TiO2+84wt%Li2ZrCl6]]> 1wt%PVDF 100nm / 20μm (lateral thickness ratio 200) 100μm (film / sheet thickness ratio 1000) 0.368 87.37 7 <![CDATA[15wt%LLTO+84wt%Li2ZrCl6(LLTO:~200GPa)]]> 1wt%TPA 50nm / 2μm (lateral thickness ratio 40) 40μm (film / sheet thickness ratio 800) 0.473 98.14 8 <![CDATA[15wt%LLTO+80wt%Li2ZrCl6(LLTO:~200GPa)]]> 5wt%TPA 50nm / 2μm (lateral thickness ratio 40) 40μm (film / sheet thickness ratio 800) 0.451 113.72 9 <![CDATA[15wt%LLTO+84.8wt%Li2ZrCl6(LLTO:~200GPa)]]> 0.2wt%TPA 50nm / 2μm (lateral thickness ratio 40) 40μm (film / sheet thickness ratio 800) 0.495 81.99 Comparative Example 1 <![CDATA[99wt%Li2ZrCl6]]> 1wt%PTFE (fiberized) / Film thickness 40μm 0.3 20.3 Comparative Example 2 <![CDATA[94wt%Li2ZrCl6]]> 6wt%PVDF / Film thickness 40μm 0.124 61.29 Comparative Example 3 <![CDATA[40wt%TiO2+59wt%Li2ZrCl6(TiO2:~282GPa)]]> 1wt%PVDF 50nm / 2μm (lateral thickness ratio 40) Film thickness 40μm (film / sheet thickness ratio 800) 0.163 55.29 Comparative Example 4 <![CDATA[30% TiO2 (nanoparticles) + 69 wt% Li2ZrCl6]]> 1wt%PVDF / Film thickness 40μm 0.272 58.31 Comparative Example 5 <![CDATA[15 wt% Li3La(PO4)2 (nanoparticles) + 80 wt% Li2ZrCl6 (Li3La(PO4)2: ~15 GPa)]]> 5wt%PVDF / Film thickness 40μm 0.339 20.1
[0164] In Table 1, the lateral thickness ratio represents the ratio of the lateral size to the thickness of the added nanosheets, and the membrane thickness ratio can represent the ratio of the thickness of the solid electrolyte membrane to the thickness of the nanosheets. It can be seen from Table 1 that compared with Comparative Examples 1-5, the composite solid electrolytes in Examples 1-9 have improved the electrical conductivity of the composite solid electrolytes while also improving the mechanical strength by adding nanosheets. In addition, the addition of nanosheets also improves the density of the electrolyte membrane and improves the safety of the composite solid electrolyte membrane. Moreover, since the entire process does not require fiberization of the binder, the production cost is reduced, the production efficiency is improved, and the stability of production is ensured.
[0165] In addition, for Ratio 3, the increase in the amount of TiO2 nanosheets added leads to a high overall Young's modulus of the solid electrolyte membrane. Under the condition of a certain binder, it is not conducive to the densification of the membrane, and the mechanical properties of the composite membrane will deteriorate.
[0166] The basic concepts have been described herein. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of the present application. Although not explicitly stated herein, those skilled in the art may make various modifications, improvements and amendments to the present application. Such modifications, improvements and amendments are suggested in the present application, so such modifications, improvements and amendments still belong to the spirit and scope of the exemplary embodiments of the present application.
[0167] At the same time, the present application uses specific words to describe the embodiments of the present application. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of the present application. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or multiple times in different positions in the present application does not necessarily refer to the same embodiment. In addition, some features, structures or characteristics in one or more embodiments of the present application can be appropriately combined.
[0168] Similarly, it should be noted that in order to simplify the description of the disclosure of this application and thus help understand one or more embodiments of the invention, in the above description of the embodiments of this application, multiple features are sometimes combined into one embodiment or its description. However, this disclosure method does not mean that the features required by the object of this application are more than the features mentioned in the claims. In fact, the features of the embodiments are less than all the features of the single embodiment disclosed above.
[0169] Finally, it should be understood that the embodiments described in this application are only used to illustrate the principles of the embodiments of the present application. Other variations may also fall within the scope of the present application. Therefore, as an example and not a limitation, the alternative configurations of the embodiments of the present application may be considered to be consistent with the teachings of the present application. Accordingly, the embodiments of the present application are not limited to the embodiments explicitly introduced and described in the present application.
Claims
1. A composite solid electrolyte, characterized in that: include: Nanosheets, which are composed of inorganic oxides, wherein the inorganic oxides include oxides of one or more metals; as well as A halide solid electrolyte; wherein: The mass proportion of the nanosheets in the composite solid electrolyte is 5-30%; The halide solid electrolyte has a chemical formula of Li a MX b represents, M represents a metal element or a metalloid element, including one or more of B, Si, Ge, As, Sb, Te, Al, Zn, Mg, Ca, Ba, Mn, Cd, Co, Yb, Y, Cr, In, Ga, Sr, Hf, Ti, Ta, Sn, Nb, Er, Sc, and Zr; X represents a halogen element; The Young's modulus of the nanosheet is greater than 80 GPa; The size of the nanosheet is 3nm-200nm in the thickness direction, and the ratio of the thickness of the nanosheet to the thickness of the composite solid electrolyte is 150-2000.
2. The composite solid electrolyte according to claim 1, characterized in that The metal includes one or more of aluminum, titanium and zirconium.
3. The composite solid electrolyte according to claim 1, characterized in that The inorganic oxide includes lithium element.
4. The composite solid electrolyte according to claim 3, characterized in that: The inorganic oxide has lithium ion conductivity, and the room temperature lithium ion conductivity is ≥10 -6 S / cm.
5. The composite solid electrolyte according to claim 1, characterized in that: The halide solid electrolyte has lithium ion conductivity, and the room temperature lithium ion conductivity is ≥10 -5 S / cm.
6. The composite solid electrolyte according to claim 1, characterized in that: The composite solid electrolyte further includes a binder, and no fiberization process occurs when the binder participates in the composition of the composite solid electrolyte.
7. The composite solid electrolyte according to claim 1, characterized in that: The composite solid electrolyte further includes a binder, and the content of the binder having a fibrillated structure in the binder does not exceed 10% of the total amount of the binder.
8. A method for preparing a composite solid electrolyte according to any one of claims 1 to 7, characterized in that: The preparation method comprises: Mixing the nanosheets and the halide solid electrolyte to obtain a mixed material under non-destructive conditions; Pressing the mixed material to prepare the composite solid electrolyte; The analytical statistical properties of the halide solid electrolyte do not change under non-destructive conditions; the analytical statistical properties include one or more of average particle size, density, gram capacity, and surface area.
9. A battery, characterized in that The battery comprises the composite solid electrolyte according to any one of claims 1 to 7 or the composite solid electrolyte prepared by the preparation method according to claim 8.
